Teprotumumab as a Novel Therapy for Thyroid-Associated Ophthalmopathy - Smith, Terry J. (Frontiers in Endocrinology, 2020)
Thyroid-associated ophthalmopathy (TAO) has remained a vexing and poorly managed autoimmune component of Graves’ disease where the tissues surrounding the eye and the upper face become inflamed and undergo remodeling. This leads to substantial facial disfigurement while in its most severe forms, TAO can threaten eye sight. In this brief paper, I review some of the background investigation that has led to the development of teprotumumab as the first and only US FDA approved medical therapy for TAO. This novel treatment was predicated on recognition that the insulin-like growth factor I receptor plays an important role in the pathogenesis of TAO. It is possible that a similar involvement of that receptor in other autoimmune disease may lead to additional indications for this and similar treatments.